Perawatan Pompa Air untuk Sarana Air Bersih Mushalla Al-Muhajirin Desa Blang Krueng Kabupaten Aceh Besar - Suhaeri; Mahdi Syukri; Alfisyahrin; Agus Adria; Syukriyadin; Masri Ali; Nurdin Ali; M. Nizar Machmud; Huzaim; Saiful; Ramdan Halid Siregar (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Community service activities are carried out to maintain water pumps in the Al Muhajirin Mushalla clean water facility in Blang Krueng Village, Aceh Besar District, to address the problem of the availability of clean water in the area. The project team carried out several stages during the week, including observation, problem identification, planning, implementation, and evaluation. Observations were made at clean water facilities to identify existing problems. The results showed that the water pump used in the clean water facility was damaged and not functioning properly. Therefore maintenance is needed to repair the water pump so that clean water facilities can function properly. After identifying the problem, the team plans to maintain the water pump by replacing damaged components and cleaning the contaminated parts. Clean water facilities in Mushalla Al Muhajirin can function properly after maintenance, and the availability of clean water in the area increases. Evaluation is carried out to determine the success of maintenance. The evaluation showed that the maintenance was successful in increasing the availability of clean water, and the local community felt that this improvement helped. In conclusion, the water pump maintenance project at Mushalla Al Muhajirin succeeded in increasing the availability of clean water. This community service project is expected to inspire and guide other communities in improving their clean water facilities.